Semi-analytical model for umbrella arch systems employed in squeezing ground conditions. (June 2016) - Oke, Jeffrey; Vlachopoulos, Nicholas; Diederichs, Mark S.
Highlights: A semi-analytical model for umbrella arch systems employed in squeezing ground. Limitations of existing analytical models for umbrella arch systems. Semi-analytical model was validated to a published case study. Abstract: Methods of approximation that predict the mechanical responses of the tunnel support systems in conjunction with ground behaviour are invaluable to the tunnel design engineer. Analytical models are often used in order to predict and/or validate ground-support behaviour. Conventionally, these analytical models do not account for the complex loading and reacting conditions of umbrella arch support systems throughout the tunnel excavation and support sequence. As such, a semi-analytical model is proposed within this paper for umbrella-arch systems that employ an umbrella ache with forepoles, in squeezing-ground conditions. The semi-analytical model is based on an assortment of applicable methods and theories depending on the relevant loading. Beam theory, elastic foundation theory, and the Convergence-Confinement Method (CCM) are all incorporated within the proposed analytical method. After a review of the literature it became apparent that a limited amount of models existed for squeezing-ground conditions. Previous models were based on gravity-driven (Silo Theory) loading conditions rather than the more applicable stress-driven (squeezing) loading conditions. The results of the semi-analytical approach included herein were able to reasonably capture the displacement profiles associated with captured field data. This semi-analytical approach can be considered for use by tunnel design engineers in order to aid them with tunnel support design.